A novel cuproptosis-related genes nomogram on the prognosis and immune microenvironment of breast invasive carcinoma - Guanmin Shang; Zhiwen Xu; Dengfu Peng; Xinghe Liao; Jiangang Zhao (Scientific Reports)
Abstract Explore the relationship between breast invasive carcinoma (BRCA) and cuproptosis-related genes (CRGs). CRGs related to prognosis were calculated using Lasso analysis and multivariate Cox analysis based on BRCA data from the TCGA, CRG signatures were then generated to categorize patients based on their risk scores into high-risk and low-risk categories. The GEO dataset was used as external validation. A nomogram was constructed in order to further predict the survival of patients. We also examined differences in the infiltrative status of immune cell subsets present between the high-risk and low-risk categories. The prognostic gene expression were validated utilizing real-time quantitative PCR (RT-qPCR). We identified nine CRGs associated with survival and built a risk model to separate patients into high - and low-risk groups with distinct differences in survival time. Risk model performance was confirmed by the ROC curve and nomogram. Additionally, we found a significant difference between the two patient groups in the extent of immune cell infiltration. qRT-PCR analysis revealed differential expression of seven CRGs (AK7, CEL, GRIA3, KCNE2, NT5C1A, PGK1, NOS1) across various breast cancer cell lines compared to MCF-10 A cells, showing both positive and negative regulation in different cell lines. These results may help illuminate the functions that CRGs perform in BRCA, which might improve our knowledge of cuproptosis and facilitate the implementation of more successful immunotherapy techniques.